Highly qualified grass hockey sportswomen`s adaptation to training intensity in the macrocycle preparatory period - Kostiukevych, V.; Shchepotina, N.; Zhovnych, O.; Shynkaruk, O.; Koliadych, Y.; Hatsoieva, L.; Voronova, V.; Vozniuk, T.; Kaplinskyi, V.; Diachenko, A.; Chernyshenko, T.; Konnova, M. (Journal of Physical Education and Sport, 2020)
The article presents the methodical approach to organizing of highly qualified grass hockey sportswomen`s adaptation to training intensity in the macrocycle preparation. Material and methods. 19 highly qualified grass hockeysportswomen have taken part in the research. The sportswomen average age is 24,5±3,1 years. Sports qualification is the Ukraine Sport Master, the Ukraine Sport Master of International Level. The research purpose is to identify and to justify the methodological approach to organizing of highly qualified grass hockey sportswomen during the preparatory period of the macrocycle considering their adaptation to athletic demands of training and competing. The research methods: analysis and summarizing of the special literature and Internet data; pedagogical observation; pulsometry; pedagogical testing; chronometery; methods of mathematical statistics. Results. Six zones of training intensity are determined: 1st - heart rate is 114-132 beeps per min/bpm (restoring demands); 2nd - 132-144 bpm(restoration-supporting demands); 3rd - 144-156 bpm(supporting demands); 4th - 156-168 bpm(developing demands); 5th - 168-180 bpm(developmental demands); 6th — 180-186 bpm(developmental demands). The various training and intensity interrelation of highly qualified grass hockey sportswomen to training intensity in the macrocycle preparation has been determined. Conclusion. Highly qualified grass hockey sportswomen`s adaptation to the athletic intensity of training and competing during the macrocycle preparatory period should be carried out according to the phase of the physical fitness development.